GC‐MS Characterization of Cyclic Fatty Acid Monomers and Isomers of Unsaturated Fatty Acids Formed During the Soybean Oil Heating Process. Issue 5 (8th April 2019) - Cherif, Ammar; Boukhchina, Sadok; Angers, Paul
Abstract : In this work, the possibility of formation and isolation of cyclic fatty acid monomers (CFAM) from polyunsaturated fatty acids via prolonged heat treatment of soybean oil are studied. The structures of CFAM are determined using Gas chromatography‐Mass spectrometry (GC‐MS) of their 4, 4‐dimethyloxazoline (DMOX) derivatives, the yield of derivatization is 98%. Among CFAM, the cyclohexyl fatty acids with ring from C12 to C17 and the cyclohexneyl with ring from C10 to C15 formed acid are detected by GC‐MS. The new cyclopentyl with ring at C14 position or between C13 to C17 are detected from linoleic acid. Also, the variation of major fatty acids composition of soybean oil during heated treatment at 150, 180, 210, and 240 °C for 60 h are analyzed. The results indicate that after heating, soybean oil contains four isomers of conjugated linoleic acid (CLA), four isomers of C18:1 and four isomers of C18:3. The heating process, the enrichment steps, and CFAM concentration can modify the profile of CFAM and permit the emergence of new compounds, which can be useful to know the edible oil structural changes during the phases of extraction and analysis. Practical Applications : When heated at high temperature for a long time, soybean oil undergoes isomerization and cyclization reactions. In fact, CFAM structures with five and six membered carbon rings are identified from heated oil. A new mass spectrum of the CFAM derivative from the intramolecular C18:2 cyclization is also described. Although CFAM are present at very low concentrations in heated oils, these compounds are the most toxic metabolites produced in soybean oil heated at high temperature. In addition to the four isomers of conjugated linoleic acid, four isomers of C18:1 and four of C18:3 are detected during the heating process. The data clearly show that it is necessary to avoid heating the soybean oil to a temperature above 210 °C for a period of more than 60 h which can minimize the production of CFAM. The gap of 68 amu between the molecular ion (333) and m/z 265 indicate the location of cyclopentyl ring at C14, which is first determined in heated soybean oil. Abstract : The gap of 68 amu between the molecular ion (333) and m/z 265 indicate the location of cyclopentyl ring at C14, which is first determined in heated soybean oil.